PENGARUH KARAKTERISTIK DAN KOMPETENSI AUDITOR PADA PERSEPSI AUDITOR ATAS EFEKTIVITAS RED FLAGS UNTUK MENDETEKSI KECURANGAN PELAPORAN KEUANGAN - Werastuti, Desak Nyoman Sri (Indonesian Journal of Accounting and Governance, 2017)
This research aims at finding empirical evidence on the influence of characteristics and competencies of auditor towards the auditors’ perception on the effectiveness of 42 red flags adopted from the Statement of Auditing Standard No. 99. The characteristics of auditors were analyzed based on gender, position, and tenure; while the competencies of the auditors were analyzed based on education, previous experience, and training on graud. Respondents of this study were 84 auditors working in 10 Public Accountant Firms in Bali. The results shows the competencies of auditors which include education, previous experience and training on fraud influence the perception of editor on the effectiveness of red flags in detecting fraud in financial reports. Other characteristics which include gender, position, and tenure of work does not influence the perception of the audditor on the red flags effectiveness in detecting fraud. In the short-term, the result of this study is espected to contribute to the knowledge on the factors that influence the auditor’s capabilities on the use of red flags. In the long term, the results are expected to give inputs to regulators and accounting profession institutions in stipulating regulations, standards, and indicators that are more implementable in detecting fraud by public accountants in Indonesia.